CONFESSION SACRAMENT IN THE ORTHODOX RITUALITY AS A FACTOR IN THE UKRAINIAN MENTALITY FORMATION IN THE 17th – 19th CENTURIES - BORODENKO, Olena; FAZAN, Vasyl (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the research is to elucidate the history of confession sacrament introduction into the socio-cultural space of the Orthodox Ukrainian population and its influence on the national mentality formation of the Ukrainians in the 17th – 19th centuries based on the materials of canonical and literary literature, directives, statutory acts, and information and publications. Research Methodology. The historical and analytical, discursive, and interdisciplinary focus of the research is determined by an extensive methodological toolkit, which is used in accordance with the research fields of individual religious and historical disciplines, using, first of all, the methods of deconstruction and critical analysis of sources. Scientific Novelty. The issue of a religious factor influence in general and in the context of the confession sacrament in particular on the formation of mass and individual forms of national self-identification of the Ukrainian population remains poorly studied. Conclusions. The installation of the procedure for introducing the holy sacraments of confession and communion into church rituals took place from the middle of the 2nd century to the 7th century, when Christian canons were established. There were three forms of the confessional rite: the confession of a Christian alone with God, a collective confession at a general prayer meeting of believers in the temple, the confession before a monk or other holy person. Over time, public confession was replaced by a private appeal of a believer to Christ through the mediation of a priest. Initially, the anonymity of a confessor was emphasized, but gradually the requirement of mandatory identification of a person and his social status was introduced. In the confessional preface, a priest listed warnings about avoiding a sinful behaviour, and separately emphasized the fulfillment of God’s instructions in various life situations. A believer could communicate with the Almighty independently through a prayer-appeal. A priest addressed God with the aim of forgiving a believer’s sins reading a specific prayer from the “Trebnyk” prayer book of 1646 by P. Mohyla. Violators of confession were prosecuted according to the norms of spiritual and civil law. A Christian who had not undergone the rite of confession could not testify under oath in court in either civil or criminal cases. The confessional rite acquired special significance in the lives of convicted and dying people. Through subtle psychic impulses, religious self-identification was affirmed, and distinctive features of individual and mass forms of the national mentality of the Ukrainians were formed. Key words: Orthodox Church, repentance, holy sacrament, priest, confession, religious rite, national mentality.